Obstacles to Learning System Innovation During The Covid-19 Pandemic in Realizing the Objectives of the Directorate of Elementary School - Isra Oktaviani; Aishya Shaharani; Ibrahim Tanebe (Institut Agama Islam Negeri Sorong, 2022)
A change, including a change in the field of education, can be said to be a form of innovation if the change is done intentionally and to improve the previous conditions to make it more profitable in order to improve a better life. Due to the Covid-19 pandemic, the government is currently moving to change the online learning system that can be done at each student's home. As a result, the use of ICT (Information and Communication Technology) is increasing. In the learning innovation that is carried out, there are various obstacles that must be passed. What are the obstacles that must be overcome and what are the solutions for related parties such as the Directorate of Elementary Schools in overcoming these obstacles and ensuring that learning innovations during the pandemic can be achieved? The purpose of this article is to understand learning innovations by the Directorate of Elementary Schools and identify and overcome obstacles to learning innovations in their application. The research method used in this study is a qualitative method. It is hoped that in the future there will be an even better online model to support learning to be more effective and efficient which can be well received by students so that the objectives of the Directorate of Elementary Schools in 2024 can be achieved.